Extreme and Highly Heterogeneous Microclimates in Selectively Logged Tropical Forests - Blonder, Benjamin; Both, Sabine; Coomes, David A.; Elias, Dafydd; Jucker, Tommaso; Kvasnica, Jakub; Majalap, Noreen; Malhi, Yadvinder Singh; Milodowski, David; Riutta, Terhi; Svátek, Martin (Frontiers in Forests and Global Change, 2018)
Microclimate within forests influences ecosystem fluxes and demographic rates. Anthropogenic disturbances such as selective logging can affect within-forest microclimate through effects on forest structure, leading to indirect effects on forests beyond the immediate impact of logging. However, the scope and predictability of these effects remains poorly understood. Here we use a microclimate thermal proxy (sensitive to radiative, convective, and conductive heat fluxes) measured at the forest floor in three 1-ha forest plots spanning a logging intensity gradient in Malaysian Borneo. We show 1) that thermal proxy ranges and spatiotemporal heterogeneity are doubled between old growth and heavily logged forests, with extremes often exceeding 45°C, 2) that nearby weather station air temperatures provide estimates of maximum thermal proxy values that are biased down by 5-10°C, and 3) that lower canopy density, higher canopy height, and higher biomass removal are associated with higher maximum temperatures. Thus, logged forests are less buffered from regional climate change than old growth forests, and experience much higher microclimate extremes and heterogeneity. Better predicting the linkages between regional climate and its effects on within-forest microclimate will be critical for understanding the wide range of conditions experienced within tropical forests.